Design, Sustainable Synthesis, Characterization, Antimicrobial Evaluation and in silico ADMET Prediction of New Functionalized Imidazolium Based Ionic Liquids - Al Johani, Anas R.; Almutairi, Saud M.; El-Sayed, Wael S.; Sahu, Pramod K.; Sahu, Praveen K.; Messali, Mouslim (Asian Journal of Chemistry, 2020)
A series of sixteen new ionic liquids (ILs) bearing imidazolium moiety were designed and synthesized under sustainable and green conditions which were confirmed by analytical and spectral techniques using 1H- & 13C-NMR, FT-IR, mass and elemental analysis. A panel of clinically isolated strains was used for in vitro inhibitory antimicrobial activities screening of synthesized ionic liquids. The results of antimicrobial assay showed that some of synthesized ionic liquids showed moderate to good activity. Among these ILs, ionic liquids 3, 4 and 5 (bearing alkyl chain with a phenyl group) significantly inhibited cell growth of strains. In this regard, these ionic liquids considered as promising antibacterial agents when compared with standard antibiotics. By encouraging in vitro antimicrobial screening, in silico ADMET evaluation has been performed and found excellent pharmacokinetic, bioavailability and toxicity profiles. Synthesized ionic liquids has found to be safe and non-toxic according to calculated in vivo computed LD50 values (2.49-2.80 mg/kg) for rat acute toxicity.